2018
DOI: 10.1159/000493754
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde Assay in the Evaluation of Aspirin Antiplatelet Effects

Abstract: Aspirin is essential in secondary prevention of patients after myocardial infarction and with coronary artery disease. However, impaired pharmacodynamic response to aspirin is frequent (high on-treatment platelet reactivity [HTPR]). This leads to an enhanced prevalence of cardiovascular events and to an impaired clinical outcome. The current specific assays to evaluate aspirin antiplatelet effects are complex, time-consuming and demand for a high laboratory expertise. Therefore, we developed a potentially beds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Oxidative stress altering platelets redox state may lead to their activation and eventually thrombus formation. It was previously observed that increased intraplatelet MDA content was also shown to be related to higher platelet activity, including aggregation [ 14 , 29 ]. This association was confirmed by the other studies that found suppression of platelet MDA levels resulted in inhibition of arachidonate- and collagen-induced aggregation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress altering platelets redox state may lead to their activation and eventually thrombus formation. It was previously observed that increased intraplatelet MDA content was also shown to be related to higher platelet activity, including aggregation [ 14 , 29 ]. This association was confirmed by the other studies that found suppression of platelet MDA levels resulted in inhibition of arachidonate- and collagen-induced aggregation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its measurement is laborious and time-consuming, also when using commercially available colorimetric assays. On the other hand, malondialdehyde (MDA), a broadly and easily assayed marker of lipid peroxidation and oxidative stress [ 13 ], is also known to be produced by the platelet’s thromboxane synthase in amounts that are equimolar to TXA 2 [ 14 ]. Therefore, the aforementioned methods may not be considered as routine studies done in all patients in the early postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance of the samples was determined at 570 nm by a microplate reader, and the quantification of nitrite in the sample was standardized with 0 - 100 mmol/L of nitrite concentration (NaNO 2 ) ( 19 ). Also, lipid peroxidation was determined on the exposed cells to the HDCCD (6a-j) ( 20 ). In this part, the MDA content of the cell supernatant and culture media on the cells was measured using TBA reaction.…”
Section: Methodsmentioning
confidence: 99%